3D Biomechanical Analysis Application Model Of Physical Condition Training In SPOBNAS Athletes - Ade Rahmat; Rio Wardhani; Ferry Marlianto (Jurnal Pendidikan Olah Raga, 2026)
This study aimed to develop and test the feasibility and effectiveness of a 3D Biomechanical Analysis Application Model for physical condition training in SPOBNAS athletes aged 14–17 years. The research employed the Borg & Gall development model through 10 systematic steps, with data collected using observation, questionnaires, tests, and documentation. Validation was conducted by three experts (material, media, and measurement), while the effectiveness test applied a quasi-experimental pretest-posttest control group design involving 50 athletes divided equally into experimental and control groups.The results showed that the application model had high validity, with an average Aiken’s V of 0.95 (material experts) and 0.93 (media experts). Practicality tests indicated that athletes (mean = 3.90) and coaches (mean = 3.88) assessed the program as very practical. Statistical analysis confirmed that the data were normally distributed (Sig. = 0.200) and homogeneous (Sig. = 0.058). The effectiveness test demonstrated a significant improvement in the experimental group (t count = 5.120 > t table = 2.009, df = 49), with a mean gain of 14.2 points compared to only 4.6 in the control group. Furthermore, effect size analysis (Cohen’s d = 1.25) indicated a large effect.In conclusion, the developed 3D Biomechanical Analysis Application Model was proven to be valid, practical, and effective, contributing positively to improving athletes’ physical fitness, motor skills, and motivation. This application can be a valuable tool for coaches in enhancing performance training and supporting athlete development at SPOBNAS.